Extract from Rosa spp. as a Factor Influencing the Growth Rate of Coagulase-Negative Staphylococcus Strains - Lidia Piekarska-Radzik; Joanna Milala; Robert Klewicki; Michał Sójka; Dorota Żyżelewicz; Bożena Matysiak; Elżbieta Klewicka (Molecules)
Coagulase-negative bacteria of the Staphylococcus genus are currently frequent food contaminants. The increase in antibiotic resistance means that these microorganisms are becoming the cause of many serious infections and toxications. Their resistance to routinely used chemical compounds has led to the search for alternative methods to combat food-borne pathogens. For this purpose, plant extracts rich in phenolic compounds are increasingly used. The aim of this study was to assess the effect of extracts obtained from the pseudo-fruits and flesh of Rosa canina, Rosa rugosa and Rosa pomifera ‘Karpatia’ on the growth dynamics of bacterial strains of the Staphylococcus genus (72-h co-culture; plate inoculation method). The conducted studies allowed us to conclude that extracts from Rosa spp. show high antistaphylococcal activity. However, it is not proportional to the dose used. Rosa spp. extracts already at concentrations of ¼ MIC limit the growth of the biomass of bacteria of the Staphylococcus genus. The above-described dependencies are very individual—strain-specific, not species-specific. However, based on SEM analysis, it can be observed that the antistaphylococcal mechanism of action of Rosa spp. extracts is associated with the coating of cell walls by the extracts and the disintegration of cell membranes, as a result of which the cells are destroyed.